Iniquities in the access to renal transplant for patients with end-stage chronic renal disease in Brazil - Elaine Leandro Machado; Waleska Teixeira Caiaffa; Cibele Comini César; Isabel Cristina Gomes; Eli Iola Gurgel Andrade; Francisco de Assis Acúrcio; Mariangela Leal Cherchiglia
The objective of this present study is to analyze individual and contextual factors associated with access to renal transplant in Brazil. An observational, prospective and non-concurrent study was carried out, based on data from the National Database on renal replacement therapies in Brazil. Patients undergoing dialysis between 01/Jan/2000 and 31/Dec/2000 were included and monitored up to the point of transplant, death or until the end of the study period. Variables that were analyzed included: individual variables (age, sex, region of residence, primary renal disease, hospitalizations); and context variables concerning both the dialysis unit (level of complexity, juridical nature, hemodialysis machines and location) and the city (geographic region, location and HDI). Proportional hazard models were adjusted with hierarchical entry to identify factors associated with the risk of transplant. The results point to differentials in access according to socio-demographic, clinical, geographic and social factors, indicating that the organ allocation system has not eliminated avoidable disparities for those who compete for an organ in the nationwide waiting list.